Evolução das relações entre cidades e portos: entre lógicas homogeneizantes e dinâmicas de diferenciação - Frédéric Monié; Flavia Nico Vasconcelos (Confins)
The current stage of globalisation presents mutations that act on the global network of long distance spatial interactions and redefine the institutional scenery, the technic-operational modalities and the spatial organisation of the world port system. The situation of the ports, through which transit substantial part of the whole goods international trade, is not less paradoxal and complex. The strategies developed by the players that control the port maritime horizon added to the strategies imposed by the economic players that control the terrestrial horizon, put the city-ports in a path marked by transport and production networks. The game of the port politics, which oscillate between competition and complementarity, consists in placing the port in the core of these networks through a rising number of economic, commercial, urban, environmental and social variables facing the functional and territorial rationalities of players that can transform the port into a simple logistic hub or the contrary, a big logistic centre. Based on the definition of commercial ports as territories situated in manoeuvre spaces of a global and regional “game board”, there are possibilities of articulations differentiated among the capabilities located in the commercial port, in the productive system and in the resources of the urban territory and of an analysis with trajectory in three scales: in the global level, through globalisation, in the middle-economic level, in the regional systems that capture the rising volumes of flows and transformation activities; and in the local level, on the territory of the city-port. This approach allows the conception of a typology of city-ports as territories of circulation and/or productive territories.